Energy transfer within responsive pi-conjugated coassembled peptide-based nanostructures in aqueous environments. Issue 2 (15th December 2014) - Ardoña, Herdeline Ann M.; Tovar, John D.
Abstract : Energy transfer is demonstrated within a responsive donor–acceptor system which incorporates two different semiconducting units (oligo( p -phenylenevinylene and quaterthiophene) coassembled within peptide nanostructures in completely aqueous environments. Abstract : Steady-state and time-resolved photophysical measurements demonstrate energy transfer within π-conjugated peptide nanostructures composed of oligo-( p -phenylenevinylene)-based donor units and quaterthiophene-based acceptor units in completely aqueous environments. These peptide-based assemblies encourage energy migration along the stacking axis, thus resulting in the quenching of donor emission peaks along with the development of new spectral features reminiscent of acceptor emission. These spectral changes were observed even at minute amounts of the acceptor (starting at 1 mol%), suggesting that exciton migration is involved in energy transport and supporting a funnel-like energy transduction mechanism. The reversibility of nanostructure formation and the associated photophysical responses under different conditions (pH, temperature) were also studied. This unique material design incorporates two different semiconducting units coassembled within peptide nanostructures and offers a new platform for the engineering of energy migration through bioelectronic materials in aqueous environments.